Phytoplankton dynamics and structure: a comparative analysis in natural and man-made water bodies of different trophic state - Naselli-Flores, Luigi; Barone, Rossella (Hydrobiologia, 2000)
Previous investigations on Sicilian man made lakes suggested that physical factors, along with the specific morphology and hydrology of the water body, are important in selecting phytoplankton species. In particular, the variations of the z sub(mix)/z sub(eu) ratio due to the operational procedure to which reservoirs are generally subject were recognised as a trigger allowing the assemblage shift. To investigate if these variations may be considered analogous to those occurring in natural lakes as trophic state and phytoplankton biomass increase, causing a transparency decrease and a contraction of the euphotic depth, phytoplankton were collected in two natural water bodies, one mesotrophic (Lake Biviere di Cesaro) the other eutrophic (Lake Soprano), and compared with those collected in two reservoirs with analogous trophic characteristics (Lake Rosamarina, mesotrophic and Lake Arancio, eutrophic). Particular attention was paid to the dynamics of two key groups: Cyanophytes and chlorophytes. In all four water bodies, transparency mainly depended on chlorophyll level. Annual average value of phytoplankton biomass in the mesotrophic environments was below 2.0 mg l super(-1), whereas in the eutrophic systems it was well above 10 mg l super(-1). All water bodies showed the presence of cyanophytes (e.g. Anabaena spp., Anabaenopsis spp., Microcystis spp., Planktothrix spp.) and chlorophytes (e.g. Chlamydomonas spp., Botryococcus spp., Oocystis spp., Scenedesmus spp., Pediastrum spp.), but their relative proportions and body size dimensions were different. In particular, small colonial chlorophytes and large-colony forming cyanophytes were most common in the most eutrophic water bodies, whereas larger colonies of green algae in those with a lower trophic state. The results showed that, under the same climatic conditions, autogenic (increase of biomass, decrease in light penetration and euphotic depth) and allogenic (use of the stored waters, anticipated breaking of the thermocline, increase of the mixing depth) processes may shift the structure of phytoplankton assemblage in the same direction even though the quantity of biomass remains linked to nutrient availability.